Caracterização de caquis ‘giombo’ e ‘rama forte’ produzidos no semiárido nordestino - Barbosa, Mayra Cristina Freitas (Universidade Federal Rural do Semi-Árido, 2019)
Persimmon (Diospyros kaki L.) crop is very expressive in the South and Southeast of Brazil. Although have been much studied, there is little knowledge about post-harvest management of fruits cultivated in other Brazilian regions. This work aimed to characterize persimmons fruits, Giombo and Rama Forte cutivars, harvested at different maturation stages, produced in the Vale do Jaguaribe, Ceará State. Fruits were harvested at three maturation stages (green, immature and ripe, classified according to the peel color) and the following characteristics were evaluated: fruit diameter, fresh weight, peel color, pulp color, firmness, pH, titratable acidity (TA), soluble solids content (SSC), TA/SSC, total sugars, reducing sugars, astringency index (AI), soluble tannins content (ST), vitamin C content, carotenoids, beta-carotene, total extractable polyphenols (TEP), total antioxidant activity (TAA-DPPH and TAA-ABTS+), pectin methylesterase (PME) and polygalacturonase (PG) activity. Two experiments were conducted to evaluate the two cultivars separately, in a completely randomized design with five replicates, three fruits each. Data were analyzed by one-way analysis of variance and Kruskal-Wallis test, and the means were grouped by Tukey test, at 5% probability, using R software version 3.5.1. Firmness and soluble solids content did not differ among maturation stages in both cultivars. However, peel color index was higher in all fruits at mature stage. AI, TEP, ST, and TAA-DPPH were lower in fruits harvested at the mature stage in both varieties. In conclusion, Giombo and Rama Forte persimmons cultivars present better physicochemical characteristics when the fruits were harvested at the mature stage, that is when peel color becomes yellowish
Keywords: Adstringência; Compostos bioativos; Diospyros kaki L.; Estádios de maturação; Astringency; Bioactive compounds; Diospyros kaki L.; Maturation stages; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA